Business Strategy Development for HAWS Home Accessories - Nur Prasetyo, Fajri; Dung DO, Anh (The Indonesian Journal of Business Administration, 2017)
Abstract. EBS is Indonesian e-reader application to find and read the replica of magazines, books and newspaper in digital format. EBS is one of FACT products that was founded in 2010. FACT is an Indonesian emerging apps company that is bridging content providers with its latest mobile technologies with great UI/UX design and data-driven to build an extensive service for our clients, either individual or enterprise. EBS e-book reader is the solution to overcome issue of declining reading interest in Indonesia which the factor is coming from nation’s cultural vitality where is having lower practice of literate behavior.  By analyzing the situation from external factor which is quite high competition within e-publishing, government support to drive digital economy, and higher funding from investor to growing digital startup, as well as internal factor which has suppliers from local and foreign publishers, having assets of cloud storage, also providing various payment method strengthened five elements to meet business strategy for increasing penetration in potential market among Z generation: targeted area where most university are located, maximizing internal development, developing adaptability and customization features, build three stages of deployment: utilizing KOL, social media and acquiring new market in high school, also set lowest cost through scale of advantages.  The business strategy is certainly supported by research methodology based on quantitative analysis in which the information is collected from two sources data: primary data by interviewing with management team from executive through managerial level and questionnaire that is addressed to 47 respondents from e-book reader customers and public, also secondary data which the data is obtained from the reference book, journal and publications. This research has the aim to identify profiling of current consumers involves living in area with higher mobilization, time behavior where they used to read at least two hours in a day, typical of book that they frequently read, most application used through what channels that they search for.  Keywords: E-book reader, Digital Economy, Z Generation, Business Strategy, Quantitative Analysis